Design of a Web Based Workshop Management Information System Application Using Rapid Application Development Techniques - Nurfathan Samnaufal Razzaq; Renny Sari Dewi (Universitas Negeri Surabaya, 2025)
The rapid pace of digital transformation across industries requires all sectors, including the automotive service industry, to adopt technology in order to enhance operational efficiency and competitiveness. This study aims to design and develop a web-based Management Information System (MIS) for CV XYZ, a workshop that has been relying on manual methods for its transaction and data recording processes. These manual practices have led to problems such as delayed recordkeeping, risk of data loss, and inaccurate inventory information. To address these issues, this research adopts a qualitative approach combined with the Rapid Application Development (RAD) method, which emphasizes speed and flexibility in system development. The process involves analyzing user needs, designing user interfaces, implementing the system, and conducting system testing. The results show that the developed web-based MIS significantly improves data management related to services, spare parts, mechanics, and transactions in a faster, more accurate, and integrated manner. User Acceptance Testing (UAT) conducted with the business owner revealed a 100% satisfaction rate with all developed system features. These findings indicate that implementing the MIS not only increases the operational efficiency of the workshop but also supports data-driven decision-making in real time. Theoretically, this research contributes to a deeper understanding of the RAD method in the context of system development for micro, small, and medium enterprises (MSMEs), and it serves as a reference for similar initiatives in other sectors.